3D printing of tablets using inkjet with UV photoinitiation - Clark, Elizabeth A.; Alexander, Morgan R.; Irvine, Derek J.; Roberts, Clive J.; Wallace, Martin J.; Sharpe, Sonja; Yoo, Jae; Hague, Richard J.M.; Tuck, Chris J.; Wildman, Ricky D. (Elsevier, 2017)
Additive manufacturing (AM) offers significant potential benefits in the field of drug delivery and pharmaceutical/medical device manufacture. Of AM processes, 3D inkjet printing enables precise deposition of a formulation, whilst offering the potential for significant scale up or scale out as a manufacturing platform. This work hypothesizes that suitable solvent based ink formulations can be developed that allow the production of solid dosage forms that meet the standards required for pharmaceutical tablets, whilst offering a platform for flexible and personalised manufacture. We demonstrate this using piezo-activated inkjetting to 3D print ropinirole hydrochloride. The tablets produced consist of a cross-linked poly(ethylene glycol diacrylate) (PEGDA) hydrogel matrix containing the drug, photoinitiated in a low oxygen environment using an aqueous solution of Irgacure 2959. At a Ropinirole HCl loading of 0.41 mg, drug release from the tablet is shown to be Fickian. Raman and IR spectroscopy indicate a high degree of cross-linking and formation of an amorphous solid dispersion. This is the first publication of a UV inkjet 3D printed tablet. Consequently, this work opens the possibility for the translation of scalable, high precision and bespoke ink-jet based additive manufacturing to the pharmaceutical sector.